Patterns and processes of the genetic diversity in crabs (Decapoda, Brachyura): integrative approach with biological, ecological, and demographic traits - Peres, Pedro Augusto da Silva (2021)
The patterns and processes of the genetic diversity (GD) are still surrounded by unresolved questions in the fields of ecology and evolution. One of the questions is what drives GD at the intra- and interspecific level. This topic needs further empirical data, especially regarding the megadiverse marine environment. In this dissertation, we used crabs (Eubrachyura) as models to test how biological, ecological, and demographic traits are associated to GD. This dissertation is composed of four chapter (one published paper, and three papers in preparation) that asked different questions within this framework. In chapter 1, we compared two phylogenetically close species (Callinectes ornatus and C. danae) to test the hypothesis that biological traits are more important than the dispersal potential explaining GD spatial patterns. We show that salinity tolerance can explain genetic structure, phylogeographic patterns, and the demographic history of both species. Considering the questions that remained unanswered, in chapter 2 we investigated the effects of the Amazon-Orinoco plume (physiological barrier) on C. ornatus employing a nextgeneration sequencing approach (ddRAD-seq) alongside with mtDNA. We show a speciation with gene flow scenario in that groups separated by the plume are differentiated, but we still find gene flow between them. In chapter 3, we investigated the GD spatial patterns using mtDNA of 14 crabs from the Western Atlantic and tested the latitudinal gradient hypothesis. Our results show that interspecific GD is higher at lower latitudes, but intraspecific patterns vary across species. Finally, in chapter 4, we investigated the association among biological and demographic traits (8 variables) with GD. We analyzed the most comprehensive dataset to date of Eubrachyura mtDNA available in public databases and generated during this dissertation (150 species) and did standardized searches in the literature looking for the biological traits. Overall, our results show that the historical effective population size is the primary factor determining crabs GD variation, but other traits might also contribute to this variation. Therefore, we are sure this dissertation opens new venues by providing novel approaches on GD patterns and processes using crabs as models, but our results might also be extended to other taxa, especially marine ones.